Pelaksanaan Edukasi Pengendalian Gula Darah Pasien Diabetes Melitus Tipe 2 di Rumah Sakit Panti Rapih Yogyakarta - Maria Meilina Ekasari; Ana Setiyorini (I Care Jurnal Keperawatan STIKes Panti Rapih, 2020)
Background: Diabetes Mellitus (DM) is a metabolic disorder caused by a reduction or absence of the insulin hormone from pancreatic beta cells, or due to impaired insulin function, or both. If the DM not managed properly can lead several of chronic disease. The education program for type 2 DM patients had been done by nurses, dietitians and doctors in outpatient department, but the quality of implementation has not been discovered. Objective: To describe the implementation of the blood glucose control health education program in patients with type 2 diabetes mellitus from the preinteraction phase to the termination phase at outpatient department in a privatehospital Yogyakarta. Methods: An observational quantitative research conducted from March to May 2019 in outpatient department in a private hospital Yogyakarta. Thirty respondents were recruit with accidental sampling technique. The inclusion criteria was nurses who provide health education to patients with type 2 DM. The observation performed during the health education session. Univariate analysis used to analysis the data. The distribution of data presented in frequency and percentage. Results: The majority of respondents (n=25; 83%) performed well, a small proportion of respondent (n=5; 17%) performed pretty good when deliver the blood sugar control health education in patients with type 2 DM from the preinteraction phase to the termination phase. Conclusion: It is necessary to improve the ability of nurses in conducting health education in patients by using standard operating procedures and conducting review of operational standard procedures. Keywords: type 2 DM, health education, blood glucose control